The blessing and turnover rites of the IBM 4381 computer system - De La Salle University, Manila (Animo Repository, 1992)
The blessing and turnover rites of the IBM 4381 Computer System which was donated by Philam Insurance Company to the Computer Services Center was blessed. DLSU President Brother Rafael S Donato, FSC presented a plaque of appreciation to Leslie Mouat, President of Philam Insurance Co. at the turnover rites.